SUSTAINABLE AGRICULTURE PRACTICES AND GREEN SKILLS FORMATION: A NARRATIVE REVIEW - Rahman, Rokani; Abd. Wahid, Nur Husna (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
The global transition toward sustainable food systems necessitates a workforce equipped with complex “green skills”, yet agricultural education often remains tethered to traditional productivism paradigms. This narrative review synthesises contemporary literature to elucidate how engagement in sustainable agricultural practices catalyses the development of green skills. By analysing the intersection of vocational training and social science, the study identifies a fundamental conceptual shift: the redefinition of the agriculturist from a mere technician to a systemic “change agent” capable of navigating socio-ecological complexities. Three dominant themes emerge from the analysis: the prioritisation of affective competencies, such as stewardship and agency, over purely technical skills; the finding that skill acquisition is mediated primarily through immersive, participatory pedagogies rather than passive instruction; and the urgent need to dissolve the historical silos separating agricultural production from environmental education. Addressing the observed “novelty plateau” where competency growth stagnates, this review proposes the Integrated Eco-Social Competency (IESC) Framework. This theoretical contribution advocates for redesigning learning environments into “living labs”, offering a strategic roadmap for policymakers to bridge the gap between sustainability mandates and practical curriculum implementation.